A high-throughput screening platform to identify MYCN expression inhibitors for liver cancer therapy - Xu, Yali; Mishra, Hricha; Furutani, Yutaka; Yanaka, Kaori; Nishimura, Hajime; Furuhata, Erina; Takahashi, Masataka; Gailhouste, Luc; Suenaga, Yusuke; Hippo, Yoshitaka; Yu, Wenkui; Matsuura, Tomokazu; et al. (Frontiers in Oncology, 2025)
MYCN, an oncogene implicated in hepatocellular carcinoma (HCC), is predominantly expressed in cancer stem-like HCC cells. It drives tumorigenicity, metastasis, and therapeutic resistance. In this study, we hypothesized that the pharmacological inhibition of MYCN could represent a novel therapeutic strategy for HCC. To identify inhibitors of MYCN expression, we developed an unbiased, high-throughput screening platform. With this platform, we identified MI202 as a potent inhibitor of MYCN expression. MI202 significantly reduced MYCN promoter activity and mRNA levels in HCC cells, inhibiting cell proliferation, spheroid formation, and colony growth and promoting apoptosis. Notably, MI202 selectively inhibited the proliferation of HCC cells but not of normal hepatic cells, highlighting its potential for HCC-specific therapy. Genome-wide CRISPR knockout screening has identified acyl-CoA thioesterase 2 (ACOT2), a key regulator of lipid metabolism, as a molecular target of MI202. ACOT2 downregulation by MI202 was associated with reduced MYCN expression, suggesting that ACOT2 may mediate MYCN-driven tumorigenesis through lipid desaturation. Overall, this study presents a robust high-throughput screening platform to identify MYCN inhibitors and highlights the potential of pharmacological downregulation of MYCN as a therapeutic strategy for targeting HCC.